Surviving the transition shock in the first year of teaching through reflective practice. (October 2016) - Farrell, Thomas S.C.
Abstract: No profession wants to admit that it 'eats its young' but research in general education has indicated that 24% of novice teachers leave teaching within the first year, 33% drop out after three years and between 40% and 50% leave within the first five years. This indicates that novice teachers may experience a difficult beginning to their teaching career. What is shocking in the field of TESOL is that we do not really know what novice ESL teachers experience in their first year of teaching, yet this knowledge is essential for both teacher educators and novice teachers alike if novice teachers are to successfully navigate this complex first year as a teacher. This paper outlines and discusses three female novice English as a second language (ESL) teachers' perceptions of their experiences during their first semester (14 weeks) of teaching in a university language school in Canada. Results indicate that in the absence of any real inductions program, the novice teacher reflection group they were members of helped the teachers better understand the many shocks they experienced so they could 'swim' rather than 'sink' in their first semester as ESL teachers.